Antiscalants in RO membrane scaling control. (15th September 2020) - Yu, Wei; Song, Di; Chen, Wei; Yang, Hu
Abstract: Reverse osmosis (RO) plays an important role in freshwater production. Mineral scaling is an inevitable problem in the RO desalination process. Various methods, including the pretreatment of feed water, the optimization of operational processes, the development of novel membrane materials, and the addition of antiscalants, have been developed to mitigate scale formation in RO systems. Among these methods, the addition of antiscalants is a relatively cost-effective and convenient technique for membrane scaling control. In the current work, various kinds of antiscalants, scale inhibition mechanisms, and their applications to RO membrane scaling control are reviewed. Weakness of existing antiscalants and challenge arising from their practical applications, such as membrane fouling caused by antiscalants, increased bacterial growth, dosing control, and the disposal of resultant concentrates, are also presented. To effectively alleviate scaling on RO membrane by using antiscalants, the development of novel, high-performance, and environment-friendly antiscalants on the basis of an in-depth study of the inhibition mechanisms and well-established structure–activity relationships is urgently necessary. The optimization of antiscalants and their combinations with other pretreatments in practical RO operations are essential in efficient scaling control. Graphical abstract: Image 1 Highlights: Characteristics of different antiscalants. Introduction of scale inhibition mechanisms and various evaluation methods. External and internal factors of antiscalants on scale control. Comparison and assessment of different antiscalants to the applications in RO systems. Prospects and technical developments of antiscalants in RO membrane scaling control.